The Role of Judges in Guaranteeing Legal Certainty and Justice: An Analysis to the Application of Judicial Independence Principle in Criminal Cases in Indonesia - Ariyanti, Vivi (International Conference of Moslem Society, 2019)
The duty and obligation of a state based on law is to provide protection for the public from all possible crimes, so that the state has a role in conducting prevention and repression of crime, and this cannot be separated from the implementation of criminal law by the state, as a tool to protect the public. The authority of the state to provide criminal sanctions is then delegated to law enforcement officers working in a system known as the Criminal Justice System. The criminal justice system itself is strongly influenced by the community environment and the field of human life. Therefore, the criminal justice system will always experience interaction, interconnection, and interdependence with its environment and sub-systems of the criminal justice system itself. One of the supporting sub-systems that have a very important role in implementing the criminal justice system is the court, which contains judges who are authorized by law to adjudicate. Judges in their capacity as authorities in the legal field have freedom as a form of independence in carrying out their duties. This independence does not mean that judges are freed from all obligations and responsibilities, but the independence of judges has the meaning of their existence as bearers of moral responsibility for upholding justice. This paper discusses the role of judges in ensuring legal certainty and justice in society, especially in handling criminal cases. This paper uses normative and philosophical analysis to the application of judicial independence principle in adjudicating criminal cases in the Indonesian criminal justice system.